Construction an expression vector and Agrobacterium tumefaciens strain carrying ZmbZIP72 gene isolated from maize - Hằng, Phạm Thị; Hạnh, Hà Hồng; Linh, Nguyễn Thùy; Hiền, Lê Thị Thu; Hải, Nông Văn; Huệ, Huỳnh Thị Thu (Vietnam Journal of Biotechnology, 2018)
In plants, members of bZIP transcription factors are involved in various biological processes such as organ and tissue differentiation or vascular development. Moreover, the basic leucine zipper (bZIP) is one of the largest transcription factor families which play an important role in environmental stress responses. However, few bZIP genes are related to abiotic stress responses. Some studies have found that transgenic plants overexpressing the bZIP genes enhanced tolerance to abiotic stresses. Several of stress-related genes in maize have been identified and characterized. A ZmbZIP72 gene belonged to A group could be strongly induced by ABA and abiotic stresses. Some previous studies have shown that overexpression of the ZmbZIP72 gene resulted in improved drought and salt tolerance of a transgenic Arabidopsis. In this work, the ZmbZIP72 gene from drought-treated maize was isolated and sequenced with 894 bp in full-length of the coding region. Nucleotide comparison of the ZmbZIP72 gene and a GenBank sequence (accession number HQ328839) revealed that two changes were found at positions 486 (A to C) and 493 (C to T), respectively. Changes in predicted amino acid sequence were at positions 102 (Lys>Asp) and 105 (Pro>Ser). The newly isolated ZmbZIP72 gene was ligated with RD29A promoter and 35S terminator to create a RD29::ZmbZIP72::35S cassette in pRTL2 vector. Afterwards, this cassette was constructed into pCAMBIA1301 and the new recombinant pCAMBIA1301 vector carrying ZmbZIP72 construct has transformed into A. tumefaciens strain EHA105 which is material for plant transformation